Farewell to oligoastrocytoma: in situ molecular genetics favor classification as either oligodendroglioma or astrocytoma - Sahm, Felix; Reuss, David; Koelsche, Christian; Capper, David; Schittenhelm, Jens; Heim, Stephanie; Jones, David T. W.; Pfister, Stefan M.; Herold-Mende, Christel; Wick, Wolfgang; Mueller, Wolf; Hartmann, Christian; et al. (Acta neuropathologica, 2014)
Astrocytoma and oligodendroglioma are histologically and genetically well-defined entities. The majority of astrocytomas harbor concurrent TP53 and ATRX mutations, while most oligodendrogliomas carry the 1p/19q co-deletion. Both entities share high frequencies of IDH mutations. In contrast, oligoastrocytomas (OA) appear less clearly defined and, therefore, there is an ongoing debate whether these tumors indeed constitute an entity or whether they represent a mixed bag containing both astrocytomas and oligodendrogliomas. We investigated 43 OA diagnosed in different institutions employing histology, immunohistochemistry and in situ hybridization addressing surrogates for the molecular genetic markers IDH1 R132H, TP53 , ATRX and 1p/19q loss. In all but one OA the combination of nuclear p53 accumulation and ATRX loss was mutually exclusive with 1p/19q co-deletion. In 31/43 OA, only alterations typical for oligodendroglioma were observed, while in 11/43 OA, only indicators for mutations typical for astrocytomas were detected. A single case exhibited a distinct pattern, nuclear expression of p53, ATRX loss, IDH1 mutation and partial 1p/19q loss. However, this was the only patient undergoing radiotherapy prior to surgery, possibly contributing to the acquisition of this uncommon combination. In OA with oligodendroglioma typical alterations, the portions corresponding to astrocytic part were determined as reactive, while in OA with astrocytoma typical alterations the portions corresponding to oligodendroglial differentiation were neoplastic. These data provide strong evidence against the existence of an independent OA entity.